2019
DOI: 10.1177/1933719118792104
|View full text |Cite
|
Sign up to set email alerts
|

Potential Marker Pathways in the Endometrium That May Cause Recurrent Implantation Failure

Abstract: The aim of this prospective cohort study was to identify altered biologic processes in the endometrium that may be potential markers of receptive endometrium in patients with repeated implantation failure (RIF) as compared with fertile controls. The study was conducted in a university-affiliated in vitro fertilization (IVF) gynecology clinic and molecular biology and genetics laboratory. Healthy fertile controls (n = 24) and patients with RIF (n = 24) were recruited. Window of implantation gene profiling assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 66 publications
0
47
0
Order By: Relevance
“…These pathways can control barrier function by altered cytoskeletal organization (Cvitic et al, 2020). Study has also shown that "Adherens junction" was associated with repeated implantation failure (Bastu et al, 2019). 'Tight junction' pathway was associated with fetal neural tube defects (Wang L. et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These pathways can control barrier function by altered cytoskeletal organization (Cvitic et al, 2020). Study has also shown that "Adherens junction" was associated with repeated implantation failure (Bastu et al, 2019). 'Tight junction' pathway was associated with fetal neural tube defects (Wang L. et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…To identify the key microRNAs of RIF, we downloaded the raw data of microarray datasets using the keywords "recurrent implantation failure" combined with "microRNA" to search for genome-wide expression studies in the Gene Expression Omnibus (GEO) database from National Centre for Biotechnology Information (NCBI). The microRNA dataset GSE71332 [16] and the gene expression dataset GSE111974 [15] were generated using the GPL18402 (Agilent-046064 Unrestricted_Human_miRNA_V19.0_Microarray) and the GPL17077 (Agilent-039494 SurePrint G3 Human GE v2 8×60K Microarray 039381)platforms, respectively. GSE71332 contained endometrial samples collected at the WOI (LH+5 to LH+9) from seven RIF patients and ve normal fertile women, while the endometrial samples collected at WOI (LH+7 to LH+10) from 24 RIF patients and 24 fertile controls were included in GSE111974.…”
Section: Microarray Dataset Collectionmentioning
confidence: 99%
“…To provide insight into the potential roles of miRNAs and their target genes causing RIF, we analysed two public microarray datasets from the Gene Expression Omnibus (GEO) database, GSE71332 (miRNA) [14] and GSE111974 (mRNA) [15], and performed integrated bioinformatics analyses to investigate the potential endometrial causes of RIF. Differentially expressed miRNAs (DEMs) and their predicted target genes were rstly identi ed between RIF and fertile control.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated complement cascade-associated genes, Serpin1, and Ube2V1 of the ubiquitination system, suggest a therapeutic approach that targets ubiquitous-altered mechanisms for better protection of stress-related progression of the disease (Sanfeliu et al, 2019 ). In regard to reproductive physiology, these three key pathways of inflammation, the proteasome, complement, and coagulation cascades were also shown to interact with circadian regulated genes in the endometrial biopsy samples isolated from female patients having repeated implantation failure (Bastu et al, 2019 ). Complement regulatory protein, MCP also known as CD46, was significantly upregulated in these patients, likely due to increased C5a/C5aR1 axis.…”
Section: Complement and Circadian Systems In Metabolic Diseasesmentioning
confidence: 99%
“…Thus, the inflammation associated with hypoxia and altered metabolite partitioning resulted in the failure of the blastocyst implantation. Importantly, angiotensin I ( AGT ), and its endopeptidase neprilysin, MME , were also upregulated in these patients, suggesting hypertension in the uterine vascular circuits may also be contributing to the failure of blastocyst implantation (Bastu et al, 2019 ).…”
Section: Complement and Circadian Systems In Metabolic Diseasesmentioning
confidence: 99%